2011
DOI: 10.1179/174329409x439023
|View full text |Cite
|
Sign up to set email alerts
|

Development of apatite coatings on Ti–6Al–7Nb dental implants by biomimetic process and EPD: in vivo studies

Abstract: This paper compares the results of the effects of a biomimetic coating and electrophoretic deposition (EPD) of hydroxyapatite (HA) on the bond strength between the bone, implant and cell compatibility of Ti-6Al-7Nb dental implants. In the biomimetic process, screw shaped implants were chemically etched and NaOH activated to form hydroxycarbonated apatite after they were soaked for six days in a solution that was five times more concentrated than regular simulated body fluid (SBF). Electrophoretic deposition wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In vivo studies performed with screw-type Ti6Al7Nb dental implants coated with HA deposited by EDP showed that these coatings lead to high integration between bone and implant by increasing the bioactivity of the implant, enhancing the mechanical properties of the screws and having a good osseointegration during the healing period compared to the uncoated ones [65].…”
Section: Alternative Deposition Techniquesmentioning
confidence: 99%
“…In vivo studies performed with screw-type Ti6Al7Nb dental implants coated with HA deposited by EDP showed that these coatings lead to high integration between bone and implant by increasing the bioactivity of the implant, enhancing the mechanical properties of the screws and having a good osseointegration during the healing period compared to the uncoated ones [65].…”
Section: Alternative Deposition Techniquesmentioning
confidence: 99%
“…The layer deposition techniques used to produce calcium phosphate include "plasma spray" [5][6][7][8] , laser ablation, "magnetron sputtering" 9,10 , sol-gel [11][12][13][14] , electrophoresis 15,16 , and biomimetic methods [17][18][19] . In the latter technique, the hydroxyapatite is precipitated from a saturated calcium phosphate solution, similar to that of blood.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The orthopedic and dental applications of HAp are limited by its poor mechanical properties. [7][8][9] Therefore, the combination of metallic implant and HAp coatings can be used in order to take advantage of the mechanical properties of substrate and the biocompatibility of HAp. [10][11][12] Among metallic implants, Ti-6Al-4V alloy has a good biocompatibility and high specific strength which has been utilised in orthopedic applications.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Among metallic implants, Ti-6Al-4V alloy has a good biocompatibility and high specific strength which has been utilised in orthopedic applications. 8,10,11 As compared with other methods that have been utilised to synthesise HAp coatings on titanium substrate, sol-gel has several advantages of changing the chemistry or processing conditions in order to modify the microstructure of coatings. [13][14][15] Furthermore, surface modification has an important role in HAp coating process on Ti-6Al-4V substrate.…”
Section: Introductionmentioning
confidence: 99%